The impact of monetary policy on banks’ profitability : evidence from 21 big european banks - Falcão, Leonor Ramos (2021)
The present Dissertation contributes to the existing empirical literature on the impact of monetary policy actions on bank profitability metrics, focusing on a sample of twenty-one European banks between Q1 2010 and Q3 2020, using quarterly data. By employing an econometric regression analysis, this Dissertation addresses the impact of conventional and unconventional monetary policy stances, controlling for macroeconomic and bank-specific variables. Data was retrieved from publicly available sources such as Eikon, OECD and FRED databases at a quarterly frequency. The main baseline findings are as follows: i) high levels of unconventional monetary policy have a negative impact on banks’ profitability, specifically, a one percentage point decrease in the difference between long- and short-term bonds’ yields leads to a decrease of 0.019pp on the banks’ return-on-assets, ii) the present empirical research cannot conclude any significant impact of conventional monetary policy level, measured by the short-term interest rate level. This article’s results are stable throughout a set of robustness checks, including i) the use of the Generalised Method of Moments (GMM) estimation, ii) a sample split between banks headquartered in Northern and Southern Europe, and iii) a change in the referenced profitability metric for the net interest income margin. The present Dissertation further discusses the impacts of its empirical findings on the future of the European banking industry and the relationship with central banks.